Nutritional profile of cancer patients treated at an outpatient oncology center in the south region of Brazil - Rebecca Dias Zaia; Antonio Augusto Claudio Pereira; Gustavo Henrique Gandolfo Souza; Gabriela Grasso Pacheco; Alvo Orlando Vizzotto Junior; Tiago Ferrari; Ricardo Andreola; Ariana Ferrari (Acta Scientiarum. Health Sciences, 2021)
To evaluate the nutritional profile of cancer patients treated at an oncology center in South Brazil. This is a descriptive, exploratory and sectional study that was developed in a process that involved 100 patients aged between 18 and 75 years old, suffering from cancer. The anthropometric variables studied were weight, height, Body Mass Index (BMI), arm circumference (AC), arm muscle circumference (AMC), triceps skinfold (TSF) and corrected arm muscle area (cAMA). For subjective nutritional assessment, we used the Patient-Generated Subjective Global Assessment (PG-SGA). Nearly half of the patients evaluated had a critical need for nutritional intervention. There was a statistically significant association between cAMA and marital status, age and gender; between AC and age, gender and staging; between AMC and staging; between BMI and marital status and age; and between TSF and marital status. Patients diagnosed with IV stage had the lowest values for nutritional variables. There was no significant association between nutritional status of patients obtained by the PG-SGA instrument and sociodemographic characteristics. Malnutrition should be diagnosed as soon as possible, aiming at early intervention and improving survival and quality of life. Therefore, early nutritional assessment in cancer patients is required, combining subjective and objective methods.